Antiangiogenesis Activity of Indonesian Local Black Garlic (Allium Sativum ‘Solo): Experiments and Bibliometric Analysis - Retno Arianingrum; Nurfina Aznam; Sri Atun; S. Senam; Alya Rizkita Irwan; Nida Qurbaniah Juhara; Nadiya Fitri Anisa; Latifah Kurnia Devani (Universitas Pendidikan Indonesia, 2023)
Cancer is still one of the leading causes of death in the world. Angiogenesis is the formation of new blood vessels, which plays a vital role in the growth of cancer cells. As a result, inhibition of proangiogenic factors such as vascular epidermal growth factor (VEGF) could be used as a cancer treatment strategy. Black garlic (BG) is processed fresh garlic (Allium sativum L.) for several days under controlled high temperature and humidity. The research aims to investigate the effect of Indonesian local BG on antiangiogenic activity through in vivo and in silico studies. The in vivo test was carried out by observing the formation of new blood vessels using the Chorio-Allantoic Membrane Assay (CAM). The in silico study was performed by docking analysis of BG bioactive compounds on the VEGF receptor (VEGFR). The results showed that ethanol extract, ethyl acetate fraction, and n-hexane fraction of BG inhibit new vessel blood formation, with n-hexane fraction having the highest efficacy. The molecular docking assay indicated some similarities in the amino acids involved in the interaction between the BG bioactive compounds and the native ligand in binding to VEGFR. This similarity may lead to interference with VEGFR resulting in angiogenesis inhibition. The study suggests that BG has the potential to be developed as an anticancer agent, which might be through the mechanism of inhibiting the angiogenesis process